Transcranial direct current stimulation and repeated sprint ability: No effect on sprint performance or ratings of perceived exertion. Issue 4 (3rd April 2022) - Alix-Fages, Carlos; Romero-Arenas, Salvador; Calderón-Nadal, Giancarlo; Jerez-Martínez, Agustín; Pareja-Blanco, Fernando; Colomer-Poveda, David; Márquez, Gonzalo; Garcia-Ramos, Amador
ABSTRACT: The role of transcranial direct current stimulation (tDCS) as an ergogenic aid is receiving attention from scientists to optimize sport performance. Most studies have examined the effects of tDCS on endurance performance during continuous tasks, while the effect of tDCS on high-intensity intermittent tasks has been less investigated. Therefore, this study aimed to explore the acute effects of tDCS on sprint performance and ratings of perceived exertion (RPE) during a repeated sprint ability (RSA) task. Twenty-five healthy males (age: 22.0 ± 2.5 years) participated in a randomized crossover study consisting of three experimental sessions (anodal, cathodal or sham tDCS) separated by 1 week. Each session consisted of (I) tDCS protocol (15 min at 2 mA applied over the dorsolateral prefrontal cortex [DLPFC]), (II) warm-up and (III) RSA task (ten 30-m running sprints separated by 30 s). Total time and RPE values were recorded for each sprint. The two-way ANOVA applied on sprint time did not reveal a significant main effect of tDCS condition ( p = .200) neither a significant tDCS condition × number of sprint interaction ( p = .716). Similarly, no significant differences were observed for the fatigue index ( p = .449), RSAmean ( p = .200) or RPE after each sprint ( p range = .116–.890). The magnitude of the differences between the tDCS conditions ranged from negligible to small (effect sizes ≤ 0.33). These results suggest that the application of tDCS over the DLPFC is not effective to increase sprint performance or reduce RPE during a RSA task. HIGHLIGHTS Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that could modulate neuromuscular performance. This study aimed to explore the short-term effects of tDCS on sprint performance and ratings of perceived exertion (RPE) during a repeated sprint ability (RSA) task. The application of either ANODAL or CATHODAL tDCS over the DLPFC for 15 minutes did not affect the sprint time of single repeated sprints or the overall metrics of RSA performance (RSAmean and fatigue index). The application of either ANODAL or CATHODAL tDCS over the DLPFC for 15 minutes did not affect the ratings of perceived exertion measured during the repeated sprints task.